Effect of carboxymethyl cellulose-based coatings incorporated with Zataria multiflora Boiss. essential oil and grape seed extract on the shelf life of rainbow trout fillets. Issue 2 (December 2015) - Raeisi, Mojtaba; Tajik, Hossein; Aliakbarlu, Javad; Mirhosseini, Seyed Hamed; Hosseini, Seyed Mohammad Hashem
Abstract To prolong the shelf life of seafood products, lipid oxidation and growth of microorganisms should be retarded. The objective of the current study was evaluating the potential application of carboxymethyl cellulose (CMC) coatings incorporated with Zataria multiflora Boiss. essential oil (ZMEO) and grape seed extract (GSE) on chemical (thiobarbituric acid reactive substances (TBARS) and total volatile basic nitrogen (TVB-N)), microbial (total viable count, lactic acid bacteria and Pseudomonas spp.) and organoleptic attributes of rainbow trout fillets during refrigerated storage for twenty days. GC–MS analysis showed that ZMEO is rich in monoterpene phenols such as thymol and carvacrol. The following results were obtained after 20 days of storage: The minimum level of TVB-N was measured in the fillets coated with CMC + 2% v/v ZMEO + 0.5% v/v GSE. The minimum number of total viable bacteria, lactic acid bacteria and Pseudomonas spp. were determined in the fillets coated with CMC + 2% v/v ZMEO + 1% v/v GSE. The fillets coated with CMC + 1% v/v ZMEO + 1% v/v GSE showed the best organoleptic properties. Our results revealed that CMC-based coatings incorporated with ZMEO and GSE could improve chemical, microbial and sensorial characteristics of rainbow trout fillets during cold storage.